The Effect Of Steeping Grated Turmeric On Blood Pressure In Hypertensive Menopausal Women: Pengaruh Seduran Parutan Kunyit Terhadap Tekanan Darah Pada Wanita Menopausal Hipertensi - Kusmiati, Lena; dinengsih, sri; Choirunnisa, Risza (Universitas Muhammadiyah Sidoarjo, 2023)
Menopause is an important phase in a womans reproductive cycle. Menopause or the cessation of menstrual periods is defined as the process of transition from productive to non-productive periods caused by decreased levels of the hormones estrogen and progesterone. This study will look at the factors that influence the effect of steeping grated turmeric on blood pressure in postmenopausal women with hypertension in Cipariuk Village,Tegal Village, Cikedal District, Pandeglang Regency, Banten.Researchers used a pre and post test design with a control group. The population in this study were all menopausal women who experienced hypertension as many as 30 people. It was carried out in March 2021. The sampling technique was total sampling divided into 2 groups, namely 15 experimental groups who were given grated turmeric 2x a day 250 cc for 7 days and 15 people in the experimental group control. Blood pressure can be lowered by steeping grated turmeric. between the control and experimental groups in postmenopausal women in Cipariuk Village, Tegal Village, Cikedal District, Pandeglang Regency, Banten in 2021 with a significance value of 0.000.There is an effect of steeping grated turmeric on blood pressure between the control and experimental groups in menopausal women. It is expected that postmenopausal women, before using blood pressure lowering drugs with chemicals, should use treatment with herbal ingredients, one of which is turmeric regularly with various processing, one of which is in the form of turmeric drinks because the ingredients are cheap and easy to obtain, especially if you have the plant.